The impact of calculation on the value of thermodynamic parameters of copper adsorption on poplar sawdust - Brdar Mirjana M.; Šćiban Marina B.; Takači Aleksandar A. (Acta Periodica Technologica, 2011)
The adsorption of Cu(II) onto poplar sawdust as an adsorbent is analyzed. The experimental data were fitted by the Langmuir isotherm using four linearized forms at the isotherm along with the original one. The least squares regression method was applied. Using the obtained Langmuir constants by each at methods, the enthalpy, entropy and Gibbs free energy at adsoption were calculated. A comparison of the used linear and non-linear regression methods in view at the goodness of the fit is presented. The coefficient of correlation was adopted as a criterionn to select the best method. The impact of the choice at regression model on the resulting estimates of the thermodynamic parameters is discussed. The best fit of the experimental data is obtained by the nonlinear regression. Thus, it is recommended to use the Langmuir parameters calculated by the nonlinear regression for estimating the thermodynamic parameters of adsorptin. The differences in the values obtained by different models are not so large to change the basic conclusion that the adsorption of copper ions on poplar sawdust is a spontaneous endothermic process i.e. that tested adsorbent has an affinity for copper ions.